"Missing perikymata"—fact or fiction? A study on chimpanzee (Pan troglodytes verus) canines. Issue 2 (18th February 2015) - Kierdorf, Horst; Witzel, Carsten; Kierdorf, Uwe; Skinner, Matthew M.; Skinner, Mark F.
ABSTRACT Recently, a lower than expected number of perikymata between repetitive furrow‐type hypoplastic defects has been reported in chimpanzee canines from the Fongoli site, Senegal (Skinner and Pruetz: Am J Phys Anthropol 149 (2012) 468–482). Based on an observation in a localized enamel fracture surface of a canine of a chimpanzee from the Taï Forest (Ivory Coast), these authors inferred that a nonemergence of striae of Retzius could be the cause for the "missing perikymata" phenomenon in the Fongoli chimpanzees. To check this inference, we analyzed the structure of outer enamel in three chimpanzee canines. The teeth were studied using light‐microscopic and scanning‐electron microscopic techniques. Our analysis of the specimen upon which Skinner and Pruetz (Am J Phys Anthropol 149 (2012) 468–482) had made their original observation does not support their hypothesis. We demonstrate that the enamel morphology described by them is not caused by a nonemergence of striae of Retzius but can be attributed to structural variations in outer enamel that result in a differential fracture behavior. Although rejecting the presumed existence of nonemergent striae of Retzius, our study provided evidence that, in furrow‐type hypoplastic defects, a pronounced tapering of Retzius increments can occur, with the striae of Retzius forming acute angles with the outer enamel surface. We suggest that in such cases the outcrop of some striae of Retzius is essentially unobservable at the enamel surface, causing too low perikymata counts. The pronounced tapering of Retzius increments in outer enamel presumably reflects a mild to moderate disturbance of the function of late secretory ameloblasts. Am J Phys Anthropol 157:276–283, 2015. © 2015 Wiley Periodicals, Inc.